AWARENESS, STRESS, ANXIETY, AND DEPRESSION AMONG HYPERTENSIVE PATIENTS ATTENDING CARDIAC OUTPATIENT DEPARTMENT IN A SUPER SPECIALTY HOSPITAL - Sharma, Sushil Kumar; Sawhney, Vineeta (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Hypertension is a major risk factor for cardiovascular disease and its association with negative emotions may increase their risk for the development of mental health disorders. The main objective of the study was to assess the awareness, stress, anxiety, and depression among hypertensive patients attending cardiac outpatient department (OPD). Methods: This study was conducted in cardiac OPD of Super Speciality Hospital associated with Government Medical College, Jammu, for a period of 1-month commencing from 1st October to 31st October 2015. Hypertensive patients were given a questionnaire regarding socio-demographic profile, risk factors, and awareness for high blood pressure, and prevalence of stress, anxiety, and depression was assessed using a structured validated questionnaire DASS-21 [depression, anxiety, and stress scale-21]. Results: It was observed that most (72.5%) of the patients were aware of symptoms and its complications and regarding psychological symptoms mild to severe depressive symptoms were present in 10%, anxiety in 70%, and stress in 10% of patients. Conclusion: There is need of psychiatric evaluation and counseling in these patients and support services to be made available to these patients. Keywords: Hypertension, Awareness, Stress, Anxiety, Depression, Depression; anxiety and stress scale-21.